EKSPLORASI VISUAL SITU CANGKUANG DALAM FOTOGRAFI SENI - Aziz, Abdul; Felix, John; Sonia, Candy Reggi (Seni Media Rekam ISI Surakarta, 2017)
The facilities and services provided by photographic technology have made it easier for people to photograph. So photography is no longer a strange thing in the society. Photography has been able to replace manual illustrations, with its many advantages, such as the similarities and details of the objects it records. Photography is also necessary as a means of communication and photographic messages can also be a means of expression. When photography enters the arts, photography can provide dimensions that touch technical aesthetic aspects, as well as conceptual and thematic discourses. Exploration Situ Cangkuang will be the choice of visual objects Researchers in the creation of artistic photography. This is a form of aesthetic expression of researchers to make a real contribution to the awakening of art treasures that touch the aspect of tourism. The research method used is the qualitative descriptive method. In this method, the researcher performs a visualization and a photographic display supported by a subjective observation result.Keywords: Photography, art, visual, and Situ Cangkuang